IMPLEMENTASI SENAYAN LIBRARY MANAGEMENT SYSTEM (SLIMS): STUDI PENELITIAN KUALITATIF - Amelia, Lidia Rizki; Permana, Hinggil; Husein, Ceceng Syarief (Information Technology Education Department, 2024)
The aim of the research is to analyze the implementation of the Senayan Library Management System (SLiMS) at Madrasah Aliyah Negeri (Man) 2 Karawang. The method used is a qualitative method with a case study approach model and literature study in this research. The data collection used is the documentation method. The data sources for this research were obtained from relevant literature such as books, academic articles and journals related to the selected topic. The results of this research are the SLiMS planning, the Principal of MAN 2 Karawang makes a time schedule, namely in the form of programs that will be planned. Such as short-term programs, medium-term programs and long-term programs. Then in the recruitment system, staff are selected according to their skills, abilities, knowledge and strong will. The implementation of the Senayan Library Management System (SLiMS) activities at the MAN 2 Karawang library has been quite effective. Since 2019 MAN 2 Karawang has been using SLiMS in library services until now. Started making barcodes for two thousand curtilage books which were revised in 2017.